Empowering Teacher in the Era of Information Technology through Self-Regulation Strategy - Maria Dewi Irawati; Pamela Hendra Heng (Journal of Communication in Scientific Inquiry (JCSI), 2024)
The pandemic has significantly transformed education, particularly in the realm of learning technology. Teachers now face the challenge of preparing lesson materials and innovating to keep pace with rapidly evolving technology while also managing student characteristics, parental expectations, and school responsibilities. The advancement of technology provides teachers with access to a wealth of information, necessitating the need to sift through and utilize accurate data to achieve educational goals. To support teachers in adapting to these changes and improving their teaching performance, this research explores the effectiveness of a self-regulation program using Mental Contrasting with Implementation Intention (MCII). The MCII program, which includes 10 items divided into three parts, was implemented with five kindergarten teachers each with over two years of experience. Evaluation data collected through descriptive qualitative analysis revealed that the program helped participants redefine their roles as educators and effectively address challenges. The study underscores the potential of self-regulation strategies in enhancing teaching practices and addressing educational challenges.